1993
DOI: 10.1177/00220345930720031401
|View full text |Cite
|
Sign up to set email alerts
|

A Histological Study of the Exfoliation of Human Deciduous Teeth

Abstract: For clarification of the histological details of the shedding of human deciduous teeth, exfoliated and extracted deciduous teeth were examined by light and electron microscopy. After the roots were completely resorbed, the dentogingival junction migrated along the inner resorbing surface and finally reached the pulpal surface of the crown. At the same time, the gingival epithelium also proliferated and migrated under the crown of the deciduous tooth in such a way that part of it lined the residue of the pulp a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
0
18
0
3
Order By: Relevance
“…Moreover, Sahara et al [33] studied the exfoliation of human deciduous teeth suggested that the internal surface of the resorbed dentin in the pulp chamber is usually repaired by deposition of cementum-like tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sahara et al [33] studied the exfoliation of human deciduous teeth suggested that the internal surface of the resorbed dentin in the pulp chamber is usually repaired by deposition of cementum-like tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We used deciduous incisors not molars because during shedding of molars the gingival tissue tends to migrate within the pulp chambers more pronouncedly making the extracted pulpal tissue less pure [17]. It was very interesting to find that only pulps from the upper not the lower incisors yielded successful cultures, we think that this could be attributed to the fact that the remaining pulp tissue in the upper incisors is larger.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda degrada pontos específicos do colágeno IV, colágenos tipos III, V, VII, XI e elastina. A reabsorção dentária fisiológica caracteriza-se como um processo programado, alternando períodos de reabsorção com períodos de repouso, configurando um caráter intermitente 20,51,67,68 . Na rizólise decídua, observa-se reabsorção dentária externa e interna como padrão de normalidade, sendo evidenciado em dentes decíduos de humanos, cães e felinos.…”
unclassified
“…Na rizólise decídua, observa-se reabsorção dentária externa e interna como padrão de normalidade, sendo evidenciado em dentes decíduos de humanos, cães e felinos. Nas fases ativas de reabsorção dentária são observadas nas superfícies radiculares, lacunas de Howship preenchidas por clastos, enquanto nas etapas de repouso observa-se formação de tecido de reparo de aspecto cementóide, podendo restabelecer as inserções periodontais 24,51,65,67,68 .…”
unclassified
See 1 more Smart Citation